Regenerative dentistry: Current and future perspectives to rejuvenate and reclaim dental tissues - Sourabh Jagannath Torvi; Kala Munniswamy (Wolters Kluwer Medknow Publications, 2014)
While widespread advances have occurred in all details of science over the past decade, regenerative dentistry has also seen its part of breakthrough innovations. Tooth regeneration offers new and innovative approaches to common problems encountered in oral and dental sciences. In cases where a tooth is lost, it may be replaced with an implant, bridge, or a denture capable of mastication. However, in many developing countries, it is often simpler (and far more cost-effective) to remove the tooth. Strategies based upon regenerative medicine that facilitates the repair or replacement of damaged teeth may hold particular promise as a means to reduce the cost of dental care. Dental maladies aside, the tooth is also a compelling candidate as a template for organogenesis which could have far-reaching implications for the field of regenerative medicine. [1] A systematic review of the literature was performed using various internet-based search engines (PubMed, Medline Plus, Cochrane, Medknow, Ebsco, Science Direct, Hinari, WebMD, IndMed, and Embase) using keywords such as "dental pulp stem cells," "regeneration," "medical applications," and "tissue engineering." This review explores existing and visionary approaches in the revolutionary field of regenerative dentistry, as an extension to the familiar concepts of regenerative medicine.